A Comprehensive Framework for Physiologically‐Based Pharmacokinetic Modeling in Matlab. (2nd April 2019) - Stader, Felix; Penny, Melissa A.; Siccardi, Marco; Marzolini, Catia
Abstract : Physiologically‐based pharmacokinetic (PBPK) models are useful tools to predict clinical scenarios for special populations for whom there are high hurdles to conduct clinical trials such as children or the elderly. However, the coding of a PBPK model in a mathematical programming language can be challenging. This tutorial illustrates how to build a whole‐body PBPK model in Matlab to answer specific pharmacological questions involving drug disposition and magnitudes of drug–drug interactions in different patient populations.